Métodos de limpeza de equipamentos industriais: destaque para o sistema CIP - Ferreira, Bianca Santos (2023)
In recent years, sanitaries demands to the production process and the final product, both by government and by consumers, have been growing more and more. One of the requirements, which makes the production and, consequently, the final product safe, it’s the way in which the equipment hygiene for this process it’s accomplished. Therefore, it’s happening an increase in the number of industries that aim to apply a standard process to their respective cleaning system. This because, currently, there are many industries that still have the sanitation done by operators, with manual work, there isn’t a pattern use quantity of cleaning agents, a standard condition time and, when there is some cleaning device installed, many times its efficiency isn’t guaranteed and often the sanitation needs to be complemented by an operator. The trend is the cleaning system to become as automated as possible, using cleaning devices that assure the maximum efficiency needed and no existing demand to use any other intervention at the sanitation process for complement. Besides that, along with the standardization of time and the quantity used of cleaning agents and predefined cleaning programs, it’s possible to decrease the operation costs, environmental impact, the need to disassemble equipment, in addition to assure its cleaning quality and, consequently, in a simple way, the final product quality. Because of that, the cleaning procedure most used, and that applies the criteria mentioned above, it’s the CIP (cleaning in place) system, which it can be implemented in automated plants or semiautomated. Usually, this implementation it’s done and required for food and beverage industries, pharmaceuticals and cosmetics, which need to accomplish a high sanitation level. The most common industries to use this system it’s the food and beverage industry, highlighted for the dairies. The CIP system consists of circle around cleaning agents, as alkaline as acids, do properly rinse and no need to disassemble any equipment and, therefore, can guarantee that won’t be any chance for contamination. In view of the above, the current graduation work aimed to carry out a bibliographical survey of the main cleaning industrial equipment methods that are available currently on the market, highlighting the CIP systems, mainly because of its functional efficiency.